CYBERSECURITY ISSUES OF MEDICAL COMPUTER SYSTEMS - Trofymenko, Olena (Ukrainian Information Security Research Journal, 2021)
In conditions of strict quarantine due to the COVID-19 pandemic, thanks to the capabilities of modern information and telecommunications systems, a significant part of medical services has been transformed into a digital environment online. The positive effect of this lies primarily in the elimination of the digital divide and realization of citizens’ rights to equal medical care in electronic format. However, this process has led to the potential danger of confidential information leaks. Nowadays, the cybersecurity issues of medical computer systems are very relevant and require a comprehensive and balanced approach to the solution. An important component is the legal protection of confidential information circulating in medical computer systems. Analysis of digital technologies and computer systems for the provision of online medical services has shown the urgency of anonymizing patients’ medical data, protecting medical devices connected to the Internet from leaks of confidential medical information. Therefore, the rules for ensuring the confidentiality of data processed in medical information systems must be strictly observed when developing appropriate software. The issue of security of the infrastructure for collection, storage and transmission of medical data is primarily to limit access and create a reliable electronic database of medical information. Certain security issues have been identified for cloud platforms used to store data in the provision of health services related to their vulnerability to possible cyberattacks. To increase the credibility and ensure the reliable protection of confidential medical information processed in such services, all software, hardware and organizational aspects should be considered. Analysis of cybersecurity of medical computer systems has identified a number of data protection issues, the importance of multifactor user authentication, access control, the use of effective cryptographic encryption schemes to effectively protect health ecosystems on the Internet and identify areas for further research to provide quality secure online health services.